DEVELOPMENT OF A STORY LEARNING MODEL USING HAND POOLS IN ELEMENTARY SCHOOLS - St. Aisyah; Edhy Rustan (Department of Pendidikan Guru Madrasah Ibtidaiyah Universitas Islam Negeri Alauddin Makass, 2023)
Abstract This study aims to analyze the need to use learning and design learning models and test the validity of storytelling learning models. The method used in this research is R&D (Research and Development) with the ADDIE development model. This research was conducted in class IV SDN 60 Salubattang, Palopo City. Data collection techniques using interviews, questionnaires, and observation. Data analysis techniques were performed by classifying the data obtained into qualitative and quantitative data. The needs analysis results illustrate that students need interesting concrete visualizations to increase interest in reading. The design of a storytelling learning model assisted by hand puppet media is described in a guidebook which contains model components, media and how to make them, and the technical application of the learning model. The learning model developed through the validation stage by design experts, material experts, linguists, and elementary school instructional practice experts obtained results that were feasible to use.